Type 2 Diabetes Mellitus Epidemiology of and its Complications - Julio Armando Sánchez Delgado; Nailé Edita Sánchez Lara (Revista Finlay, 2022)
Background: the number of people with diabetes mellitus worldwide has quadrupled in the last three decades and is currently the ninth leading cause of death. Objective: to determine the epidemiology of type 2 diabetes mellitus. Method: a descriptive, analytical, retrospective, case/control study was carried out at the César Fornet Frutos Polyclinic in the Banes municipality, from September to December 2021. The universe included all individuals diagnosed with the disease. By simple random sampling, a sample of 27 cases was obtained and the control group was formed at a ratio of 2:1, which included 54 individuals with no history of the disease. The statisticians were used: Chi square, Odd Rattio, confidence index, probability and attributable percentage risk and the association between variables was established. The analyzed variables were: sex and age, risk factors, associated diseases and complications of the disease. Results: the age groups of 60-69 years old, 70 years old and over (29.6 %) were representative. The female sex prevailed (55.5 %). The risk factors obtained significant statistical values: inadequate diet (X2=59.28 OR=16.5), obesity (X2=13.06 OR=3.22), family history (X2=8.91 OR=0, 38) and dyslipidemias (X2=1.21 OR=1.4). Ischemic heart disease (39.5 % X2=7.1 RAP=23.4 %), arterial hypertension (23.4 % X2=45.6) and bronchial asthma (16 % X2=74.6) were the associated diseases of higher incidence. Complications with increasing prevalence were: diabetic nephropathy and lactic acidosis (X2=39.1), ischemic heart disease (X2=26.7 OR=33) (X2=26.7 OR=33) and nonketotic hyperosmolar state (X2 =21.4). Conclusions: diabetes mellitus is a complex, multifactorial disease prone to complication.